Метод пошуку першого наближення для розв’язання задачі шахтної сейсмічної томографії в неоднорідному середовищі - Литвин, О.М.; Драгун, В.В. (Управляющие системы и машины, 2016)
Предложен новый метод поиска первого приближения при исследовании внутренней структуры прямоугольного тела по времени прихода сейсмической волны от источников к приемникам. Проведен вычислительный эксперимент. Запропоновано новий метод пошуку першого наближення при дослідженні внутрішньої структури прямокутного тіла за часом приходу сейсмічної хвилі від джерел до приймачів. Проведено обчислювальний експеримент. Introduction. The mineral resources extraction can be observed worldwide. Since the error in determining the mineral resources location may result the losses, it is obvious, that a necessity for the reliable methods search of the mineral resources exploration appears. Purpose of the research is to analyze the literature on mineral exploration, to study the method of finding a first approximation, to carry out computational experiments and to study new method of finding a first approximation to solve the mine seismic tomography problem. Methods: studying and generalization of advanced experience, literature analysis, method of algorithmization. The results and conclusions. A method of the plane problem solving of mine seismic tomography is presented. It is based on the solution in the form of finite sums of Fourier. The Fourier coefficients are calculated using the passage of the seismic waves known time from the sources to the seismometers.